2003
DOI: 10.1538/expanim.52.387
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Serum C-Reactive Protein (CRP) in Healthy Beagle Dogs of Various Ages and Pregnant Beagle Dogs

Abstract: Serum C-reactive protein (CRP) concentrations in healthy beagle dogs of various ages and in pregnant beagles were measured by enzyme-linked immunosorbent assay (ELISA). Serum CRP concentrations were 1.5-16.0 µg/ml (mean 7.9 ± 3.4 µg/ml) in male, and 1.8-18.9 µg/ml (mean 8.3 ± 4.0 µg/ml) in female dogs. No significant sex-related differences were observed in the values. Further, there were no significant age-related differences either. Serum CRP concentrations increased during pregnancy. The concentration of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 14 publications
4
53
2
1
Order By: Relevance
“…The concentrations of CRP in control dogs, which ranged from 0.6 to 8.8 mg/ml, are in general agreement with many studies 11,19,27,29 but disagree with others 24 that reported lower ranges for this protein in healthy dogs. Figure 2 shows the variability chart for CRP and triglycerides in both groups, where the points, range bars (which include maximum, median, and minimum quantiles), and cell means can be observed.…”
supporting
confidence: 81%
“…The concentrations of CRP in control dogs, which ranged from 0.6 to 8.8 mg/ml, are in general agreement with many studies 11,19,27,29 but disagree with others 24 that reported lower ranges for this protein in healthy dogs. Figure 2 shows the variability chart for CRP and triglycerides in both groups, where the points, range bars (which include maximum, median, and minimum quantiles), and cell means can be observed.…”
supporting
confidence: 81%
“…1 Serum CRP concentrations are not influenced by age and sex. 2 Serum CRP has shown potential as a prognosticator for survival in some neoplastic conditions such as lymphoma, ovarian cancer, thymic cell carcinoma, pancreatic cancer, and colorectal cancer. 3 Serum CRP concentration is a novel parameter to monitor response to therapy in various inflammatory conditions and to monitor response to treatment and relapse status in dogs with lymphoma.…”
mentioning
confidence: 99%
“…The inflammatory response at implantation was followed by an increase in serum C-reactive protein in the dog (Concannon et al, 1996). Although measurement of acute phase proteins has been suggested as a method of pregnancy diagnosis since pregnancy specific increase in circulating concentrations was observed (Eckersall et al, 1993) yet a reliable test is not available notwithstanding further research in this area (Kuribayashi et al, 2003;Ulutas et al, 2009).…”
Section: Acute Phase Proteinsmentioning
confidence: 99%